Pengawasan Kepala Tata Usaha Terhadap Pengelolaan Kearsipan - Devisia, Melani; Arwan, Arwan; Kanada, Rabial (El-Idare: Jurnal Manajemen Pendidikan Islam, 2025)
Orderly and systematic records management is one of the key factors in supporting the effectiveness of educational administration in schools. The success of records management is strongly influenced by the supervisory function carried out by the Head of Administration as the person responsible for school administration. This study aims to analyze the supervision conducted by the Head of Administration over records management at SMA Nurul Iman Palembang and to identify the factors influencing the implementation of such supervision. The study employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation, with the Head of Administration and administrative staff serving as the main informants. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that supervision of records management by the Head of Administration has been implemented through the establishment of work standards, monitoring of implementation, evaluation, and the provision of guidance to staff. However, the supervision has not been fully optimal due to time constraints, high workload, limited archival competencies among some staff members, and the suboptimal use of archival technology. Supporting factors include the existence of school regulations and leadership support, while inhibiting factors include limitations in human resources, facilities and infrastructure, and work culture. Thus, the supervision carried out by the Head of Administration plays a strategic role in ensuring the effectiveness of school records management.